Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper examines implications for long-term bond yields in case of Japan. The analysis finds that so far, upward pressure on interest rates from high public debt has been offset by domestic factors, including a stable investor base with a preference for safe assets. As these effects could decline with population aging, yields could rise unless reforms are implemented to stimulate growth and reduce the public debt-to-GDP ratio. In such a scenario, long-term Japanese government bond rates would remain relatively low and stable. The paper also analyzes to what extent rising health care spending poses a fiscal risk to Japan's economy.